A PREVENTIVE TREATMENT OF CHILDREN AND ADOLESCENT WITH A HIGH RISK FOR TUBERCULOSES - L. V. Poddubnaya; T. A. Panina; V. I. Bardin (Бюллетень сибирской медицины, 2013)
The aim of the work is to find an optimal combination of treatment-and-health-improving activities for the preventive treatment. There are four groups of children with the different levels of the risk: very high, high, medium and low. The most important factors of the morbidity are the following: a contact with a bacteria-excreting person and with MDR, social disadvantage, hyperergic reactions. An essential condition of an effective prevention is a realization of the treatment-and-health-improving activities for the strengthening of the resistance of the body for the tuberculosis infection. The chemoprophylaxis had been realizing for 3 or 6 months according to the following developed modes: “0A”, “0Б”, “0B”. Children from the family contact with MDR got isoniazid 15 mg/kg weight and ethambutol or pyrazinamide.